Micro-nano high-temperature-resistant superconductive ceramic VOCS waste gas catalytic treatment process

Through molecular engineering treatment of the surface of micro-nanoparticles and molecular engineering design of the pore interface, the exposure and distribution of the catalyst active sites are optimized, which solves the problems of low catalyst activity, poor selectivity and insufficient stability in the existing VOCs catalytic treatment process, and realizes efficient, energy-saving and safe VOCs waste gas treatment.

CN120618238APending Publication Date: 2025-09-12JIANGSU WEIYUAN KEPIN ENVIRONMENTAL ENGINEERING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510987491.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The existing VOCs catalytic treatment process has low catalyst activity, poor selectivity, insufficient stability, low reactor mass and heat transfer efficiency, high energy consumption, and safety needs to be improved.

Method used

The VOCS waste gas catalytic treatment process using micro-nano high-temperature resistant superconducting porcelain is optimized through surface molecular engineering treatment of micro-nano particles, self-assembly of surface micro-nano particles, molecular engineering design of pore interfaces and catalytic oxidation treatment to optimize the exposure and distribution of active sites of the catalyst, improve the dispersion and stability of active components, and optimize the mass and heat transfer efficiency of the reactor.

Benefits of technology

It significantly improves the catalytic activity and selectivity, enhances the stability and utilization efficiency of the catalyst, optimizes the mass transfer and heat transfer efficiency, reduces energy consumption and improves the safety of the system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120618238A_ABST
    Figure CN120618238A_ABST
Patent Text Reader

Abstract

The invention discloses a VOCS waste gas catalytic treatment process for micro-nano high-temperature-resistant superconducting porcelain. The VOCS waste gas catalytic treatment process comprises the following steps: S1, micro-nano particle surface molecular engineering treatment; s2, self-assembly of surface micro-nano particles; s3, pore interface molecular engineering design; and S4, carrying out catalytic oxidation treatment on the VOCs. The invention relates to the technical field of volatile organic compounds (VOCs) waste gas purification treatment, in particular to a micro-nano high-temperature-resistant superconductive ceramic VOCS waste gas catalytic treatment process, which has the following advantages: 1, the catalytic activity and selectivity are obviously improved; 2, the stability and the utilization efficiency of the catalyst are improved; 3, optimizing mass transfer and heat transfer efficiency; 4, the safety is enhanced; and 5, the energy-saving potential is great.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of volatile organic compound (VOCs) waste gas purification treatment, in particular to a micro-nano high-temperature resistant superconducting porcelain VOCS waste gas catalytic treatment process. Background Art

[0002] Volatile organic compounds (VOCs) are a common type of air pollutant, primarily originating from industries such as the chemical, coating, and printing industries. They pose a threat to human health and can also cause environmental problems such as photochemical smog. Currently, VOC treatment technologies primarily include adsorption, absorption, and catalytic oxidation. Catalytic oxidation is widely used due to its high purification efficiency and lack of secondary pollution.

[0003] However, existing catalytic oxidation technology has the following shortcomings: the catalyst activity is relatively low, resulting in a high VOCs ignition temperature and high energy consumption; the catalyst has poor selectivity for specific VOCs molecules, making it difficult to adapt to the treatment of complex exhaust gases; the catalyst active components have low dispersion and poor stability, and are easily ineffective due to high temperature or poisoning; the mass and heat transfer efficiency in the reactor is low, and there are internal diffusion limitations, which affect the overall reaction kinetics.

[0004] Therefore, developing a VOCs catalytic treatment process that can improve catalyst activity and selectivity, enhance stability, and optimize mass transfer and heat transfer efficiency has become a technical problem that needs to be urgently solved in this field. Summary of the Invention

[0005] In view of this, the present invention aims to provide a micro-nano high-temperature resistant superconducting porcelain VOCS waste gas catalytic treatment process, aiming to solve the problems of low catalyst activity, poor selectivity, insufficient stability, low reactor mass and heat transfer efficiency, high energy consumption and safety needs to be improved in the existing VOCs catalytic treatment process.

[0006] The technical solution of the embodiment of the present invention is achieved as follows:

[0007] The VOCS waste gas catalytic treatment process using micro-nano high-temperature superconducting porcelain includes the following steps: S1. Molecular engineering treatment of the surface of micro-nano particles: chemical modification is used to regulate the surface atomic / molecular structure of the catalyst active components. By controlling the type of modifier and reaction conditions (temperature 20-60°C, reaction time 1-4 hours), the exposed number and distribution of active sites are optimized;

[0008] S2. Surface self-assembly of micro-nanoparticles: The active component particles treated in S1 are mixed with a self-assembly agent, added to a superconducting porcelain carrier, and reacted at 50-100°C for 2-8 hours to construct a highly ordered and stable micro-nanoactive particle array on the carrier surface.

[0009] S3. Molecular engineering of pore interfaces: A pore template is added to the system obtained in S2. After stirring and mixing, the mixture is sintered at 500-1000°C for 2-6 hours to construct a composite pore structure with optimized pore size distribution (1-100 nm), tortuosity, and surface chemical properties.

[0010] S4. VOCs catalytic oxidation treatment: The catalyst treated in S3 is loaded into the reactor, the exhaust gas flow rate is controlled to 1-10m / s, and the reaction temperature is 100-400℃, so that the VOCs exhaust gas passes through the catalyst layer for catalytic oxidation and decomposition.

[0011] Preferably, the modifier used in the chemical modification method described in S1 is an organic compound containing sulfur and nitrogen, which regulates the electron cloud density of the surface atoms of the active component through coordination to enhance the catalytic selectivity for specific VOC molecules of benzene series and alcohols, wherein the regulation of benzene series is achieved by changing the steric hindrance of the active site.

[0012] Preferably, the self-assembly agent in S2 is a silane coupling agent. By controlling the active particle concentration to 0.01-0.1 mol / L and the amount of the self-assembly agent to 5%-20% of the mass of the active particles, the dispersion of the active components is increased by more than 50% and a stable three-dimensional array structure is formed.

[0013] Preferably, the pore template agent in S3 is carbon nanotubes or mesoporous molecular sieves. By adjusting the mass ratio of the template agent to the carrier (1:5-1:20) and the sintering heating rate (5-10℃ / min), a composite pore with a tortuosity ≤ 2 is constructed to promote the diffusion of reactants (VOCs / O2) to the active sites and the desorption of reaction products (CO2 / H2O).

[0014] Preferably, the superconducting porcelain carrier is made of a composite of aluminum oxide and zirconium oxide, and has a temperature resistance greater than 1000°C. After being treated with S2, the high temperature stability of the active particle array on the carrier surface remains unchanged for 1000 hours at 800°C.

[0015] Preferably, the reactor in S4 is a honeycomb structure with a channel cross-sectional size of 5-10 mm, a catalyst loading of 30%-50% of the reactor volume, and a reaction heat recovery rate of more than 80% achieved by a built-in heat exchange device in the reactor.

[0016] Preferably, when the VOCs concentration in S4 is ≥1000mg / m 3 By adjusting the thickness of the reactor insulation layer (50-100mm) and the exhaust gas residence time (0.5-2s), the system can achieve self-heating operation relying on the reaction heat without the need for external heating, reducing energy consumption by more than 40% compared with traditional processes.

[0017] Preferably, the catalyst active components include Pt, Pd noble metals, and may also include MnO2, CeO2 transition metal oxides, wherein the noble metals are loaded by impregnation method with a loading amount of 0.1-1wt%; the transition metal oxides are loaded by coprecipitation method with a loading amount of 5-20wt%.

[0018] Preferably, the VOCs concentration at the inlet of S4 is 100-15000 mg / m 3 , Under the condition of reaction temperature of 200-400℃, VOCs waste gas treatment efficiency is ≥99%, outlet concentration is ≤10mg / m 3 , and no thermal NOx was generated as detected by gas chromatography.

[0019] Preferably, it is suitable for the purification of methanol and ethanol waste gas generated by the chemical industry, toluene and xylene waste gas generated by the coating industry, and acetone waste gas generated by the printing industry. The processing air volume range is 1000-500000m 3 / h.

[0020] The embodiment of the present invention adopts the above technical solution, which has the following advantages:

[0021] 1. Significantly improved catalytic activity and selectivity: Through precise control of the surface structure of the catalyst's active components through surface molecular engineering of micro-nanoparticles, the exposure and distribution of active sites are optimized, significantly improving the catalytic activity and selectivity for specific VOC molecules. Experimental data show that for xylene, at a device temperature of 298°C and a flow rate of 261L / min, the inlet concentration is 289mg / m 3 The outlet concentration is only 0.8 mg / m 3 For ethanol, under certain conditions, the inlet concentration is 1355 mg / m 3 The outlet concentration can still be maintained at 0, which fully demonstrates the high catalytic activity.

[0022] 2. Improved Catalyst Stability and Utilization Efficiency: Surface micro-nanoparticle self-loading technology creates a highly ordered and stable array of micro-nanoactive particles on the carrier surface, significantly improving the dispersion, utilization efficiency, and long-term structural stability of the active components. Combined with the superior performance of superconducting ceramic materials, the catalyst maintains stable operation even under harsh conditions such as high temperatures, extending its service life.

[0023] Optimized mass and heat transfer efficiency: The composite pore structure, engineered through molecular engineering of the pore interface, promotes the diffusion of reactants and the desorption of products, eliminating internal diffusion limitations and improving overall reaction kinetics. Furthermore, the highly efficient mass and heat transfer structure, constructed using proprietary assembly technology, optimizes reactor performance and enables more efficient reactions.

[0024] 4. Enhanced safety: The low ignition temperature and good thermal stability of the superconducting ceramic catalyst reduce the risk of "temperature runaway", and the anti-poisoning ability reduces the hidden dangers of system loss of control, which essentially improves the safety of the treatment process.

[0025] 5. High Energy Saving Potential: The low ignition temperature significantly reduces preheating energy consumption. The efficient reaction heat release and recovery design enables self-heating operation of the system, reducing operating costs. For example, when processing ethanol, efficient processing and low energy consumption can be achieved under appropriate conditions.

[0026] The above summary is for illustrative purposes only and is not intended to be limiting in any way. In addition to the illustrative aspects, embodiments and features described above, further aspects, embodiments and features of the present invention will be readily apparent by reference to the accompanying drawings and the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or technical descriptions. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 is a process flow chart of the present invention;

[0029] Figure 2 Schematic diagram of the catalyst structure of the present invention;

[0030] Figure 3 This is a schematic diagram of the operation of the reactor of the present invention. DETAILED DESCRIPTION

[0031] Hereinafter, only certain exemplary embodiments are briefly described. As will be appreciated by those skilled in the art, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and description are to be considered as illustrative in nature and not restrictive.

[0032] It should be noted that the terms "first," "second," "symmetrical," "array," etc. are used only to distinguish descriptions from positional descriptions and should not be understood as indicating or implying relative importance or implicitly indicating the number of the technical features indicated. Therefore, limitations on features such as "first" and "symmetrical" may explicitly or implicitly include one or more of these features; similarly, when the number of certain features is not limited in the form of words such as "two" or "three," it should be noted that these features also explicitly or implicitly include one or more of the number of features.

[0033] In the present invention, unless otherwise expressly specified or limited, terms such as "installation," "connection," and "fixation" should be understood broadly; for example, they may refer to fixed connection, detachable connection, or integral molding; they may refer to mechanical connection, direct connection, welding, or indirect connection through an intermediate medium; they may refer to internal communication between two components or interaction between two components. Those skilled in the art will be able to understand the specific meanings of the above terms in the present invention based on the specification and drawings in conjunction with specific circumstances.

[0034] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0035] like Figure 1-3 The present invention provides a process for catalytic treatment of exhaust gas using micro-nano high-temperature superconducting porcelain VOCS, comprising the following steps: S1. Surface molecular engineering of micro-nano particles: chemical modification is used to regulate the surface atomic / molecular structure of the catalyst active components, and the number and distribution of active sites are optimized by controlling the type of modifier and reaction conditions (temperature 20-60°C, reaction time 1-4 hours);

[0036] S2. Surface self-assembly of micro-nanoparticles: The active component particles treated in S1 are mixed with a self-assembly agent, added to a superconducting porcelain carrier, and reacted at 50-100°C for 2-8 hours to construct a highly ordered and stable micro-nanoactive particle array on the carrier surface.

[0037] S3. Molecular engineering of pore interfaces: A pore template is added to the system obtained in S2. After stirring and mixing, the mixture is sintered at 500-1000°C for 2-6 hours to construct a composite pore structure with optimized pore size distribution (1-100 nm), tortuosity, and surface chemical properties.

[0038] S4. VOCs catalytic oxidation treatment: The catalyst treated in S3 is loaded into the reactor, the exhaust gas flow rate is controlled at 1-10 m / s and the reaction temperature is controlled at 100-400°C, and the VOCs exhaust gas is catalytically oxidized and decomposed through the catalyst layer;

[0039] Through precise step-by-step control from S1 to S4, from atomic-level optimization of the catalyst's active sites to engineered pore structure design, and finally to system integration for catalytic oxidation, a complete technical chain of "activity regulation - structural stabilization - mass transfer optimization - efficient reaction" has been formed. This systematic design not only ensures efficient exposure of the catalyst's active components, but also solves the problem of balancing activity and stability in traditional processes through ordered structure and pore design, providing full-process technical support for the efficient treatment of VOCs.

[0040] The chemical modification method in S1 uses sulfur- and nitrogen-containing organic compounds as modifiers. The electron cloud density of the surface atoms of the active component is regulated through coordination to enhance the catalytic selectivity for specific VOC molecules such as benzene series and alcohols. The regulation of benzene series is achieved by changing the steric hindrance of the active site.

[0041] In S1, chemical modification with sulfur- and nitrogen-containing organic compounds precisely regulates the electron cloud density and steric hindrance of the surface atoms of the active components, significantly enhancing the catalyst's targeted catalytic ability for specific VOC molecules such as benzene and alcohols. This selective optimization allows the process to specifically enhance the decomposition efficiency of key pollutants when treating complex exhaust gases, avoiding the significant differences in the treatment effects of traditional catalysts on different VOCs and improving purification accuracy.

[0042] The self-assembly agent in S2 is a silane coupling agent. By controlling the active particle concentration to 0.01-0.1 mol / L and the amount of the self-assembly agent to 5%-20% of the mass of the active particles, the dispersion of the active components is increased by more than 50%, and a stable three-dimensional array structure is formed.

[0043] In S2, by controlling the active particle concentration, the amount of self-assembly agent, and the reaction conditions, a highly ordered array of micro-nanoactive particles is formed on the support surface. This not only increases the dispersion of the active components by over 50%, but also enhances the exposure efficiency of the active sites through the ordered structure. This design not only improves catalyst utilization (reducing active component waste), but also extends the catalyst's lifespan through the stable three-dimensional array structure, reducing the cost of frequent catalyst replacement.

[0044] The S3 mesoporous channel template is a carbon nanotube or mesoporous molecular sieve. By adjusting the mass ratio of the template to the carrier (1:5-1:20) and the sintering heating rate (5-10°C / min), a composite channel with a tortuosity of ≤ 2 is constructed to promote the diffusion of reactants (VOCs / O2) to the active sites and the desorption of reaction products (CO2 / H2O).

[0045] By regulating the proportion of pore templates and optimizing sintering parameters in S3, composite pores with a tortuosity of ≤2 are constructed, significantly shortening the diffusion path of reactants (VOCs / O2) to the active sites while accelerating the desorption rate of reaction products (CO2 / H2O). This optimization of mass transfer efficiency effectively eliminates the problem of incomplete reaction caused by "internal diffusion limitations" in traditional reactors, making the catalytic reaction more thorough and improving the overall processing rate.

[0046] The superconducting porcelain carrier is made of a composite of alumina and zirconia, and its temperature resistance is greater than 1000°C. After S2 treatment, the high-temperature stability of the active particle array on the carrier surface remains unchanged for 1000 hours at 800°C.

[0047] The superconducting ceramic carrier, made of a composite of alumina and zirconia, has a temperature resistance exceeding 1000°C, and the active particle array exhibits no significant change after 1000 hours at 800°C, significantly improving the process's adaptability to high-temperature industrial environments. This high stability ensures that the process will not experience catalyst failure due to high temperatures during long-term continuous operation, reducing production losses caused by equipment failure and making it suitable for industrial-scale application.

[0048] The reactor in S4 is a honeycomb structure with a channel cross-sectional size of 5-10 mm. The catalyst loading is 30%-50% of the reactor volume. The reaction heat recovery rate is more than 80% through the built-in heat exchange device in the reactor. When the VOCs concentration in S4 is ≥1000 mg / m 3 By adjusting the thickness of the reactor insulation layer (50-100mm) and the exhaust gas residence time (0.5-2s), the system can achieve self-heating operation by relying on the reaction heat without external heating. Compared with the traditional process, the energy consumption is reduced by more than 40%. The VOCs concentration in S4 is 100-15000mg / m 3 , Under the condition of reaction temperature of 200-400℃, VOCs waste gas treatment efficiency is ≥99%, outlet concentration is ≤10mg / m 3 , and no thermal NOx is generated as detected by gas chromatography;

[0049] The honeycomb reactor's structural design and built-in heat exchange device achieve more than 80% reaction heat recovery, combined with VOCs concentration ≥1000mg / m 3 The self-heating operation mode reduces energy consumption by more than 40% compared with the traditional process; at the same time, the treatment efficiency is more than 99%, ≤10mg / m 3 The low outlet concentration and lack of thermal NOx generation ensure that exhaust gas emissions meet standards while avoiding secondary pollution. This combination of "high efficiency + energy saving + environmental protection" perfectly solves the pain points of traditional catalytic oxidation processes, which suffer from high energy consumption and the tendency to generate secondary pollution.

[0050] The active components of the catalyst include Pt and Pd noble metals, and may also include MnO2 and CeO2 transition metal oxides, wherein the noble metals are loaded by impregnation method at a loading amount of 0.1-1wt%; the transition metal oxides are loaded by coprecipitation method at a loading amount of 5-20wt%;

[0051] The active catalyst components include precious metals such as Pt and Pd, as well as transition metal oxides such as MnO2 and CeO2. The loading methods and loading amounts for these different components are clearly defined, allowing the process to flexibly adjust the catalyst formulation based on the target (e.g., high-concentration benzene series or low-concentration alcohols). This diverse selection not only ensures efficient treatment of different VOCs, but also balances catalytic activity and cost through precise loading control (e.g., transition metal oxides reduce precious metal usage), improving the process's economics and adaptability.

[0052] It is suitable for the purification of methanol and ethanol waste gas generated by the chemical industry, toluene and xylene waste gas generated by the coating industry, and acetone waste gas generated by the printing industry. The processing air volume range is 1000-500000m 3 / h;

[0053] The process is applicable to many industries such as chemical industry, coating, printing, etc., and the air volume can be handled from 1000 to 500000m 3 / h, meeting the low-volume needs of small and medium-sized enterprises while also adapting to the high-volume processing scenarios of large industrial plants. This broad applicability overcomes the "limited scenario" problem of traditional VOCs treatment technology, significantly enhancing the promotional value of the process and providing a unified solution for VOCs treatment across different scales and industries.

[0054] In this embodiment, the present invention works by combining a pre-prepared micro-nano high-temperature superconducting ceramic catalyst with a honeycomb reactor to introduce VOCs waste gas into the system and achieve efficient purification through catalytic oxidation reaction. The specific working process and parameters are as follows:

[0055] 1. Catalyst Preparation

[0056] The catalyst used in the present invention is prepared by the following steps to ensure efficient catalytic activity against VOCs such as xylene, ethanol, and benzene:

[0057] 1.1S1: Molecular Engineering of Micro-Nanoparticle Surfaces

[0058] Selecting precious metals such as Pt and Pd or transition metal oxides such as MnO2 and CeO2 as active components, and using sulfur- and nitrogen-containing organic compounds (such as thioglycolic acid) as modifiers, the surface atomic / molecular structure of the active components is regulated through chemical modification. For example, when treating Pt particles, a Pt(NO3)2 solution is mixed with thioglycolic acid in a 1:1 mass ratio and stirred at 30°C for 2 hours to optimize the distribution of active sites for benzene derivatives. When treating MnO2, MnO2 powder is mixed with the modifier in a 10:1 ratio and stirred at 50°C for 3 hours to enhance its adsorption activity for alcohols.

[0059] 1.2S2: Surface micro-nanoparticles autonomously loaded

[0060] The active component particles treated with S1 are mixed with a silane coupling agent (5%-20% of the mass of the active particles), and then added to an alumina-zirconia composite superconducting porcelain carrier (temperature resistance > 1000°C). The mixture is reacted at 50-100°C for 2-8 hours to form an ordered array of active particles on the carrier surface.

[0061] 1.3S3: Molecular Engineering of Pore Interfaces

[0062] Add carbon nanotubes or mesoporous molecular sieves as pore templates to the carrier obtained in S2 (mass ratio of template to carrier is 1:5-1:20), stir and sinter at 500-1000℃ for 2-6h (heating rate 5-10℃ / min) to form composite pores with a pore size of 1-100nm and a tortuosity ≤2.

[0063] 2. VOCs catalytic oxidation treatment

[0064] The above catalyst was loaded into a honeycomb reactor (channel cross-section 5-10mm). The treatment process and effect for different VOCs exhaust gases are as follows:

[0065] 2.1 Xylene waste gas treatment

[0066] Inlet parameters: inlet concentration 125-289mg / m 3 , flow rate 261-395L / min (corresponding cross-sectional wind speed 0.59-0.82m / s);

[0067] Reaction conditions: The device temperature is controlled at 296-303°C (maintained at around 300°C), and the heating power is 3.5KW;

[0068] Treatment effect: outlet concentration 0.4-1.1 mg / m 3 , processing efficiency ≥99.2%.

[0069] 2.2 Ethanol waste gas treatment

[0070] Inlet parameters: inlet concentration 426-1355mg / m 3 , flow rate 159-418L / min;

[0071] Reaction conditions: minimum heating temperature ≥ 230°C (outlet concentration increases when the temperature is lower than 230°C), heating power 1.1KW (without insulation) or 3.3KW (in insulation state);

[0072] Treatment effect: When the flow rate is ≤388L / min and the temperature is ≥290℃, the outlet concentration is 0.

[0073] 2.3 Ethyl acetate and benzene waste gas treatment

[0074] Ethyl acetate treatment: inlet concentration 1721-4359 mg / m 3 , flow rate 247-342L / min, temperature ≥280℃, outlet concentration is 0 (such as Experiment 3 Group 3, flow rate 302L / min, temperature 322℃, inlet 4359mg / m 3 , exit 0);

[0075] Benzene treatment: inlet concentration 2005-15000mg / m 3 , flow rate 272-383L / min, temperature ≥290℃, outlet concentration is 0 (such as Experiment 4 Group 5, flow rate 272L / min, temperature 310℃, inlet 15000mg / m 3 , outlet 0), reflecting the ability to handle high-concentration VOCs.

[0076] 3. Summary of implementation effects

[0077] The present invention can stably treat VOCs waste gases such as xylene, ethanol, ethyl acetate, benzene, etc. through the above steps, with a treatment efficiency of ≥99% and an outlet concentration of ≤1.1mg / m 3 , and can operate continuously at a flow rate of 0.6-0.8m / s and corresponding temperature conditions, adapting to the large-scale needs of industrial waste gas purification.

[0078] The following are several other specific embodiments of the present invention:

[0079] Example 1: Methanol waste gas treatment in the chemical industry

[0080] 1. Exhaust gas parameters

[0081] Imported methanol concentration 500-1200 mg / m 3 (Simulating exhaust gas from a chemical synthesis workshop), flow rate 200-300 L / min (corresponding cross-sectional wind speed 0.65-0.75 m / s), inlet temperature 45°C.

[0082] 2. Reaction Conditions

[0083] Catalyst: Pd / CeO2 composite active component modified in step S1 (Pd loading 0.5wt%, CeO2 loading 15wt%), self-loading in S2 (silane coupling agent dosage 8%) and pore design in S3 (mesoporous molecular sieve template agent, pore size 30-50nm);

[0084] Reactor temperature: 240-260°C;

[0085] Heating power: 2.0KW (heat preservation state).

[0086] 3. Treatment effect

[0087] When the inlet concentration is 800 mg / m 3 , flow rate 250L / min, temperature 250℃, outlet concentration 0.3mg / m 3 , processing efficiency 99.96%;

[0088] After 500 hours of continuous operation, the outlet concentration rose to 0.5 mg / m 3 , activity retention rate is above 95% (reflecting the stability of the superconducting porcelain carrier).

[0089] Example 2: Treatment of acetone waste gas in the printing industry

[0090] 1. Exhaust gas parameters

[0091] Imported acetone concentration 1500-3000mg / m 3 (printing ink volatile gas), flow rate 300-350L / min (cross-sectional wind speed 0.72-0.78m / s), inlet temperature 50℃.

[0092] 2. Reaction Conditions

[0093] Catalyst: MnO2 / Al2O3 treated with nitrogen-containing modifier in step S1 (MnO2 loading 20 wt%), S2 self-loading temperature 80°C, S3 pore tortuosity 1.6;

[0094] Reactor temperature: 260-280°C;

[0095] Heat recovery design: Utilize the heat exchange device in the reactor (recovery rate 85%) to achieve self-heating operation (when the concentration is ≥2000mg / m 3 No external heating is required).

[0096] 3. Treatment effect

[0097] Inlet concentration 2500mg / m 3 , flow rate 320L / min, temperature 270℃, outlet concentration 0.6mg / m 3 , processing efficiency 99.97%;

[0098] Corresponding to the data of 2025.5.818:00 in document 1 (entry 2020mg / m 3 , export 0.63mg / m 3 ), proving that mass transfer matches reaction efficiency at high concentrations.

[0099] Example 3: Treatment of mixed VOCs waste gas

[0100] 1. Exhaust gas parameters

[0101] Imported mixed VOCs (toluene 30%, ethanol 40%, acetone 30%) concentration 900-1400ppm (about 2500-3800mg / m 3 ), flow rate 148-154Nm 3 / h (corresponding flow rate 350-360L / min), inlet temperature 45-48℃

[0102] 2. Reaction Conditions

[0103] Catalyst: The composite active layer modified in step S1 (the upper Pt layer targets benzene series, and the lower MnO2 layer targets alcohols / ketones), and the S3 channel adopts a gradient pore size design (10-20nm for the surface layer and 50-80nm for the inner layer);

[0104] Reactor temperature: 300-320°C (taking into account the high temperature requirements of benzene series and the low temperature activity of alcohols);

[0105] Operating parameters: fan frequency 20Hz, heating temperature PV380-381℃ (matching the given temperature SV380℃).

[0106] 3. Treatment effect

[0107] Inlet concentration 1409.001ppm (about 3800mg / m 3 ), the outlet concentration is 0.6ppm (about 1.6mg / m3), and the treatment efficiency is 99.96%;

[0108] NO concentration 1.3-1.45 mg / m 3 , no secondary pollution, in line with ultra-low emission requirements.

[0109] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various modifications and substitutions within the technical scope disclosed in the present invention, and such modifications and substitutions are intended to be within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be subject to the scope of protection of the claims.

Claims

1. Micro-nano high-temperature superconducting porcelain VOCS waste gas catalytic treatment process, characterized by: The following steps are involved: S1. Molecular Engineering of Micro-Nanoparticle Surfaces: Chemical modification is used to regulate the surface atomic / molecular structure of the catalyst's active components. By controlling the type of modifier and reaction conditions, the number and distribution of active sites can be optimized. S2. Surface self-assembly of micro-nanoparticles: The active component particles treated in S1 are mixed with a self-assembly agent, added to a superconducting porcelain carrier, and reacted at 50-100°C for 2-8 hours to construct a highly ordered and stable micro-nanoactive particle array on the carrier surface. S3. Molecular engineering of pore interfaces: A pore template is added to the system obtained in S2. After stirring and mixing, the mixture is sintered at 500-1000°C for 2-6 hours to construct a composite pore structure with optimized pore size distribution, tortuosity, and surface chemical properties. S4. VOCs catalytic oxidation treatment: The catalyst treated in S3 is loaded into the reactor, the exhaust gas flow rate is controlled to 1-10m / s, and the reaction temperature is 100-400℃, so that the VOCs exhaust gas passes through the catalyst layer for catalytic oxidation and decomposition.

2. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The modifiers used in the chemical modification method described in S1 are organic compounds containing sulfur and nitrogen. The electron cloud density of the surface atoms of the active components is regulated through coordination to enhance the catalytic selectivity for specific VOC molecules such as benzene series and alcohols. The regulation of benzene series is achieved by changing the steric hindrance of the active sites.

3. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The self-assembly agent described in S2 is a silane coupling agent. By controlling the active particle concentration to 0.01-0.1 mol / L and the amount of self-assembly agent to 5%-20% of the mass of the active particles, the dispersion of the active components is increased by more than 50% and a stable three-dimensional array structure is formed.

4. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The pore template agent in S3 is carbon nanotubes or mesoporous molecular sieves. By adjusting the mass ratio of the template agent to the carrier and the sintering heating rate, a composite pore with a tortuosity ≤ 2 is constructed to promote the diffusion of reactants to the active sites and the desorption of reaction products.

5. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The superconducting porcelain carrier is made of a composite of aluminum oxide and zirconium oxide, and has a temperature resistance of more than 1000°C. After being treated with S2, the high-temperature stability of the active particle array on the carrier surface remains unchanged for 1000 hours at 800°C.

6. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The reactor in S4 is a honeycomb structure with a channel cross-sectional size of 5-10 mm. The catalyst loading is 30%-50% of the reactor volume. The reaction heat recovery rate reaches more than 80% through the built-in heat exchange device in the reactor.

7. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: In S4, when the VOCs concentration is ≥1000mg / m 3 By adjusting the thickness of the reactor insulation layer and the residence time of the exhaust gas, the system can achieve self-heating operation relying on the reaction heat without the need for external heating, reducing energy consumption by more than 40% compared with traditional processes.

8. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1 is characterized by: The active components of the catalyst include Pt and Pd noble metals, and may also include MnO2 and CeO2 transition metal oxides, wherein the noble metals are loaded by impregnation method with a loading amount of 0.1-1 wt%; the transition metal oxides are loaded by coprecipitation method with a loading amount of 5-20 wt%.

9. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1, characterized in that: The VOCs concentration at the inlet of S4 is 100-15000 mg / m 3 , Under the condition of reaction temperature of 200-400℃, VOCs waste gas treatment efficiency is ≥99%, outlet concentration is ≤10mg / m 3 , and no thermal NOx was generated as detected by gas chromatography.

10. The micro-nano high-temperature superconducting porcelain VOCS exhaust gas catalytic treatment process according to claim 1, characterized in that: It is suitable for the purification of methanol and ethanol waste gas generated by the chemical industry, toluene and xylene waste gas generated by the coating industry, and acetone waste gas generated by the printing industry. The processing air volume range is 1000-500000m 3 / h.